The female medical workforce - Critchley, J.; Schwarz, M.; Baruah, R. (Anaesthesia, 2021)
Summary In the UK, the proportion of female medical students has remained static over the last decade, at around 55%; however, at consultant level, only 36.6% of doctors are women. The reasons for this drop in numbers are not clear. Given the increase in number of female doctors in training, the proportion of female doctors at consultant level is lower than might be expected. This article discusses issues affecting the female medical workforce in anaesthesia, intensive care and pain medicine. It explores how gender stereotypes and implicit gender bias can affect the way women are perceived in the workplace, especially in leadership positions, and discusses health issues particular to the female medical workforce. While the issues in this article may not affect all women, the cumulative effect of being subject to gender stereotypes within a workplace not designed to accommodate the health needs of women may contribute to a work environment that may promote the attrition of women from our specialties.